PERAN HAKIKAT SAINS DALAM PEMBELAJARAN IPA TERHADAP HASIL BELAJAR SISWA - Mubarakah, Rumaisya Hanifah; Putri, Syahiida Aliyya; Wulandari, Annisa; Ikmawati, Ikmawati; Kurniawan , Kurniawan (Journal of Sustainable Transformation, 2025)
This study aims to analyze the role of the Nature of Science (NOS) in science learning and its contribution to student learning outcomes through a literature review. This study examined eight articles published between 2020 and 2025 that discussed the implementation of Nature of Science (NOS) in science education. Thematic analysis indicates that integrating NOS encompassing processes, products, applications, and scientific attitudes has a consistently positive impact on conceptual understanding, scientific literacy, critical thinking skills, and learning motivation. Additionally, inquiry-based learning and the constructivist paradigm can enhance the role of Nature of Science (NOS), making science education more contextual, interactive, and meaningful. Nonetheless, the primary challenges still stem from teachers' limited understanding and students' low levels of scientific literacy. Integrating the nature of science into science education can provide a strategic foundation for preparing students to become scientifically literate, critical thinkers, and adaptable to the challenges of the 21st century.